Study of biochar in cementitious materials for developing green concrete composites - Ravi Patel; Jarvis Stobbs; Bishnu Acharya (Scientific Reports)
Abstract Biochar is a waste biomass derived carbon enriched solid material that is capable for carbon sequestration. This study illustrates a revolutionary study on the waste biomass pyrolyzed biochar-based concrete with 0–5 wt% cement replacement by the biochar as a potential binder material without using any petroleum-derived superplasticizer. The mechanical strength properties along with the water absorption of the proposed hybrid composite are evaluated for a fixed concrete composition. Moreover, the volumetric property of the formed concrete is determined using the synchrotron-based micro-computed tomography. This study revealed that biochar incorporation up to optimum concentration helps in enhancing the mechanical strength properties of concrete. The optimum dosage of biochar which is 2 wt% increases the compressive strength, splitting tensile strength, and flexural load at fracture by 18.95%, 19.64%, and 12% respectively. Moreover, the optimum sample has shown lowest water absorption among all other samples which indicated reduced porosity in the concrete with biochar introduction. X-ray diffraction analysis confirmed the more production of calcium-silicate-hydrate hydration products for the optimum biochar-augmented concrete composites which resulted in high strength concrete formation. However, the higher concentration of biochar seemed to have negative influence on the strength and durability properties of the concrete which can be seen in terms of physical strength properties and water absorption data. Nonetheless, our novel design of biochar-based concrete can open up a new field of biochar application in construction materials without sacrificing its mechanical strength and water absorption properties to develop green concrete composites.